Analisis Gaya Kalimat Berita dan Kalimat Non-Berita dalam Teks Sastra: Kajian Kritik Stilistika - Alvin Tubagus Cahya Nugraha; Muhammad Wildan Taufik; Muhammad Zainur Rofiq; Rizaldy Satria Wiwaha (MAN 4 Kota Pekanbaru, 2026)
This study aims to comprehensively examine the use of news and non-news sentences in literary texts, including the identification of form, distribution, stylistic function, and their relationship with the formation of meaning, character characterization, and narrative dynamics. The approach used is qualitativedescriptive with a stylistic perspective, which allows an in-depth analysis of sentence units in the form of declarative, interrogative, imperative, and exclamative. The data is sourced from purposively selected Indonesian literary works, with collection techniques in the form of reading-notes and coding. The analysis is carried out through an interactive model that includes reduction, presentation, and reflexive conclusion drawn. The results of the study show that the use of sentences in literary texts is systematic and has a significant stylistic function. News sentences serve as the foundation of a stable and informative narrative, while non-news sentences enrich expressive, emotional, and communicative dimensions. The interaction of the two forms a balance between clarity of meaning and aesthetic beauty, while also reinforcing the reader's interpretive experience.